Predictive Risk Factors Associated with Severe Radiation-Induced Mucositis in Nasopharyngeal or Oropharyngeal Cancer Patients: A Retrospective Study - Yumiko Kawashita; Sakiko Soutome; Masahiro Umeda; Toshiyuki Saito (Biomedicines, 2022)
Radiation-induced mucositis in head and neck cancer patients generates difficulties in eating and swallowing, and may influence treatment tolerance, compliance, and quality of life. However, predictive factors have not been studied in detail. Thus, the aim of this study was to describe the association between pre-radiotherapy clinical factors and the incidence of severe radiation-induced mucositis in nasopharyngeal or oropharyngeal cancer patients. This retrospective study included all patients with definitive radiotherapy or chemoradiotherapy for nasopharyngeal or oropharyngeal cancer between July 2011 and June 2021 in a single center. The eligibility criteria included patients who received oral management during radiotherapy. Exclusion criteria was patients who received postoperative radiotherapy. The data were acquired from the medical records of patients. One hundred patients were included in this retrospective study. Grade 3 radiation-induced mucositis occurred in 47 patients (47%). Lymphocyte count was significantly associated with grade 3 mucositis (OR = 0.40; 95% CI = 0.19–0.86; p = 0.018). It is suggested that pre-radiation lower lymphocyte counts are a predictive risk factor for severe mucositis in patients who undergo definitive radiotherapy or chemoradiotherapy for nasopharyngeal or oropharyngeal cancer